2020
DOI: 10.1111/jace.17171
|View full text |Cite
|
Sign up to set email alerts
|

Dye degradation and bacterial disinfection using multicatalytic BaZr0.02Ti0.98O3 ceramics

Abstract: The piezocatalytic, photocatalytic, and piezo‐photocatalytic properties of BaZr0.02Ti0.98O3 (BZT) were examined for degradation of organic dyes and killing of bacteria present in the wastewater. Poled and unpoled powder samples were investigated using rhodamine‐B (RB), methyl orange (MO) dyes, and gram‐negative Escherichia coli in simulated water. The poled BZT sample demonstrated significant degradation of RB and MO dyes as compared to the unpoled BZT sample during piezocatalytic, photocatalytic, and piezo‐ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…Finally, in addition to further developing the reported various applications so far, the potentially related application fields can also be expanded according to the properties of pyroelectric materials, such as medical health monitoring, the night vision device, controllable deicing of equipment surface, electrochemical effect of pyroelectric materials for converting CO 2 into CH 4 , simultaneous monitoring and elimination of indoor methanal gas, etc, which are all closely related to the sustainable development of green energy and environmental. It is believed that pyroelectric PZT [1] Microwire Power generation PZT [18] Nanosheet Hydrogen generation PZT [105] Film Power generation Black [17] phosphorene Nanosheet Hydrogen generation ZnO [41] Nanowire Power generation BST [19] Nanoparticle Hydrogen generation PVDF [109] Film Power generation CdS [20] Nanorod Hydrogen generation PVDF [108] Nanofiber Power generation PVDF/PZT [125] Film Hydrogen generation BaTiO 3 [55] Ceramic Power generation NaNbO 3 [24] Nanorod/sheet/cube Dye degradation PZT [1] Microwire Temperature sensor NaNbO 3 [22] Nanofiber Dye degradation PMN-PT [109] Ribbon Temperature sensor BaTiO 3 [125] Nanowire Dye degradation BaTiO 3 [52] Ceramic Temperature sensor BST [129] Nanoparticle Dye degradation ZnO [13] Nanowire IR photodetector BZT [27] Ceramic Dye degradation ZnO [11] Nanowire UV photodetector LiNbO 3 [25] Nanoparticle Sterilization BiFeO 3 [14] Ceramic UV photodetector LiTaO 3 [25] Nanoparticle Sterilization P(VDF-TrFE) [116] Film Thermal imaging BZT [27] ceramic Sterilization LiNbO 3 [112] Crystal Bolometer PVDF [6] Film Temperature management Reproduced with permission. [27] Copyright 2020, American Chemical Society.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, in addition to further developing the reported various applications so far, the potentially related application fields can also be expanded according to the properties of pyroelectric materials, such as medical health monitoring, the night vision device, controllable deicing of equipment surface, electrochemical effect of pyroelectric materials for converting CO 2 into CH 4 , simultaneous monitoring and elimination of indoor methanal gas, etc, which are all closely related to the sustainable development of green energy and environmental. It is believed that pyroelectric PZT [1] Microwire Power generation PZT [18] Nanosheet Hydrogen generation PZT [105] Film Power generation Black [17] phosphorene Nanosheet Hydrogen generation ZnO [41] Nanowire Power generation BST [19] Nanoparticle Hydrogen generation PVDF [109] Film Power generation CdS [20] Nanorod Hydrogen generation PVDF [108] Nanofiber Power generation PVDF/PZT [125] Film Hydrogen generation BaTiO 3 [55] Ceramic Power generation NaNbO 3 [24] Nanorod/sheet/cube Dye degradation PZT [1] Microwire Temperature sensor NaNbO 3 [22] Nanofiber Dye degradation PMN-PT [109] Ribbon Temperature sensor BaTiO 3 [125] Nanowire Dye degradation BaTiO 3 [52] Ceramic Temperature sensor BST [129] Nanoparticle Dye degradation ZnO [13] Nanowire IR photodetector BZT [27] Ceramic Dye degradation ZnO [11] Nanowire UV photodetector LiNbO 3 [25] Nanoparticle Sterilization BiFeO 3 [14] Ceramic UV photodetector LiTaO 3 [25] Nanoparticle Sterilization P(VDF-TrFE) [116] Film Thermal imaging BZT [27] ceramic Sterilization LiNbO 3 [112] Crystal Bolometer PVDF [6] Film Temperature management Reproduced with permission. [27] Copyright 2020, American Chemical Society.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some pyroelectric materials with ferroelectric property, such as BaZr 0.02 Ti 0.98 O 3 (BZT) ceramic, can also be used for killing bacteria and organic dye decomposition based on photocatalytic and piezoelectric effect. [27] As shown in Figure 16a, under UV illumination for 90 min, the unpoled BZT ceramic has no obvious effect on bacteria survival, while the poled BZT ceramic exhibits a high bacterial killing rate of 95%, which attributes to the catalytic reaction of UV light-induced charge separation on surface. Based on ultrasonication-induced piezo-catalysis, the survival rate of E. coli under different catalysis time is illustrated in Figure 16b, we can see that the bacterial mortality rate is almost 100% based on poled BZT ceramic after 90 min of piezocatalysis, and while the unpoled BZT ceramic shows lower bacteria killing rate of 35%.…”
Section: Sterilization and Disinfectionmentioning
confidence: 98%
See 1 more Smart Citation
“…6,7 Piezocatalysis is one of the emerging fields where piezoelectric materials participate in catalytic reactions for organic pollutant degradations. [8][9][10][11] This is a kind of coupling among mechanical-electrical-chemical fields and was observed particularly in non-centrosymmetric semiconductors. Researchers have reported various traditional piezoelectric materials such as BaTiO 3 , ZnO, Ba 0.5 Sr 0.5 TiO 3 , LiNbO 3 , BiFeO 3 , KNbO 3 , NaNbO 3 , MoS 2 , and LiTaO 3 for piezocatalysis applications.…”
Section: Introductionmentioning
confidence: 99%
“…5 Some of the unexplored issues are quantitative role of piezoelectric nature, role of semiconductor nature, and effectiveness of piezocatalytic for degradation of various organic pollutant such as bacterial cell, dyes, pharmaceuticals etc. [10][11][12] Most of the recent studies have reported piezocatalysis using BaTiO 3 , Sr 0.7 Ba 0.3 Nb 2 O 6 , Bi 4 Ti 3 O 12 , LiNbO 3 , K 0.5 Na 0.5 NbO 3 , Bi 0.5 Na 0.5 TiO 3, Pb(Zr,Ti)O 3 , Ba 0.85 Ca 0.85 Ti 0.90 Zr 0.10 O 3 (BCZTO), and ZnO. [13][14][15][16][17][18][19][20][21] Among these, BaTiO 3 is the simplest, traditional, and important ferroelctric ceramics.…”
Section: Introductionmentioning
confidence: 99%